عقد العمل قيد التجربة : دراسة مقارنة - د. خالد محمد الموتى; علياء غازي طاهر (PROSPECTIVE RESEARCHES, 2023)
The contract being tested is undecisine, it gives the right to the one who does the test and has the right to put an end to it during the testing period without any warning or without a reward or compensation. So the lawful description for this contract is arousing a lengthy philological dispute which raised new opinions and thoughts about deterring the legal situations of this contract which may be considered an introductory contract or a suspended contract on the invalid conditions or a suspended contract which is in the abbrogating conditions. It is staled philologically and legally that on the time of this contract on the abbrogating all this opionion is common to the people. Because the case of unsatifaction whether by the owner towards the worker or the worker towards the owner. Since this contract should be implemented as soon as it is signed. So failure of testing leads to abbrogate the contract which is under test without any effect which opposes with the nature of this contract especially if it goes on with the ending of the date of the condition and not in the date and the contract itself.